The story of codebreaking from ancient ciphers to quantum cryptography - Cimino, Al (Arcturus, 2017)
This is a history of cryptology from its early days in Ancient Egypt, Sparta and Rome to the present day when it has ceased to be a government monopoly and now affects all our lives whenever we use our cell phones or connect to the internet. Subjects covered here include Mary Queen of Scots' cryptic messages when she was plotting against her cousin Elizabeth I; the codes used by George Washington and the Popes for military and political purposes; code-breaking during World Wars I and II including the Enigma Machine and the interception of Japanese messages before Pearl Harbor. Those who invent codes and those who break them are remarkable, indefatigable characters